(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2025)
Understanding the few minutes of our universe is important in our quest to discover the origins of electric charge. The electric charge began in the early universe during the first few minutes. The first moments after the Big Bang are called the quark-gluon plasma phase. During this phase, there are two distinct periods. The first occurs immediately after the universe’s start. The temperatures are so high during the first few minutes that quarks and gluons form strings. The top quark and antibottom quark are strings during this time in the early universe. As they collide, they start to spin, oscillate, and rotate, eventually merging into a single quark. This heavy quark, called the CD-quark, was responsible for developing electric charges in the early universe. Changes in the mass of the CD-quark are the true origin of electric charges. Electric charge is not dependent on mass, but rather on the mass change that occurred during the early universe. The CD-quark spins faster than the speed of light and vibrates in different modes, leading to the creation of electrons, protons, and neutrons. If it rotates clockwise, it generates a negative charge and shifts its vibration mode to produce an electron. An electron is not a fundamental particle. If it spins counterclockwise, it creates a positive charge and shifts into a proton. Some CD-quarks do not spin, resulting in a third vibration mode that creates a neutron. The CD-quark is a heavy quark; however, it is unique because the quark and antiquark are composed of different quarks. This property is crucial for the creation of electric charges and the formation of fundamental particles in the early universe. The CD-quark is the only source of electrons, protons, and neutrons during the first few minutes after the universe begins. After that, CD-quarks cease to exist. Charged particles have finite lifetimes; they are not stable like other particles.